Blind separation algorithm of PCMA signals with different symbol rates based on DG-PSP - Yi-ming GUO; Hua PENG; Yong YANG; Xue-juan WEI; Hao WANG (Tongxin xuebao)
A blind separation algorithm was proposed for PCMA signals with different symbol rates based on double grid per-survivor processing (DG-PSP).The channel states and two input signal components were treated as two dynamic grids,receiving mixed-signal reconstructed by respectively iterative updating the two groups of grid status,thus achieving blind signal separation.The joint iterative decoding separation structure was focused,and a detailed analysis and comparison under different error estimation of parameters was shown.The complexity of the algorithm is similar to the traditional PSP algorithm.Simulation results show that,a gain of about 2 dB in signal-noise ratio can be obtained after the first iteration at a bit error rate of 10−2,and a gain of nearly 3 dB in signal-noise ratio can be obtained after the second iteration.